1984
DOI: 10.1139/m84-048
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and cell envelope associations of flagellar basal complexes of Vibrio cholerae and Campylobacter fetus

Abstract: To isolate intact flagella with basal complexes from Vibrio cholerae, a rhamnolipid hemolysin from Pseudomonas aeruginosa was used to disrupt the cell envelope and flagellar sheath. The nonionic detergent, Triton X-100, provided similar results for Campylobacter fetus. Each of these basal complexes possessed, in addition to the four classical rings, concentric membrane rings (CMR's) similar to those found in Aquaspirillum serpens. Through the use of stereo imaging (which allows structures to be visualized in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…This structure has been described as an extension of the outer membrane, although in some cases it has been shown to be unique in composition (Doig & Trust, 1994;Fuerst, 1980 Thomashow & Rittenberg, 1985a). Electron microscopy studies of a number of organisms with polar flagella have identified, in addition, a unique basal body structure which appears to be a convex disk situated below the outer membrane (Engelhardt et al, 1993;Ferris et al, 1984;Thomashow & Rittenberg, 1985b). It remains to be established if this is an integral component of all polar structures and what role it contributes to the functioning of the polar flagellum.…”
Section: Flagellar Structuresmentioning
confidence: 99%
“…This structure has been described as an extension of the outer membrane, although in some cases it has been shown to be unique in composition (Doig & Trust, 1994;Fuerst, 1980 Thomashow & Rittenberg, 1985a). Electron microscopy studies of a number of organisms with polar flagella have identified, in addition, a unique basal body structure which appears to be a convex disk situated below the outer membrane (Engelhardt et al, 1993;Ferris et al, 1984;Thomashow & Rittenberg, 1985b). It remains to be established if this is an integral component of all polar structures and what role it contributes to the functioning of the polar flagellum.…”
Section: Flagellar Structuresmentioning
confidence: 99%
“…Some evidence exists that the polar basal-body structure differs from that of peritrichously inserted flagella. Two models for the basal organelle of polar flagella have been derived from electron microscopy studies of V. cholerae, Campylobacter fetus, Bdellovibrio bacteriovorus, and Wolinella succinogenes (44,46,180). In W. succinogenes, electron micrographs display a beautiful large basal disk described as an archimedian spiral (44).…”
Section: The Basal Bodymentioning
confidence: 99%
“…In W. succinogenes, electron micrographs display a beautiful large basal disk described as an archimedian spiral (44). Such elements, which also have been described as concentric membrane rings, were found associated with the basal organelle of Aquaspirillum serpens, V. cholerae, and C. fetus (36,46). Regardless of whether the flagellum is sheathed or unsheathed, all of the studies report the existence in the basal body complex of a large convex disk situated below the outer membrane, and thus the large disk does not seem to be a feature specific to sheath formation.…”
Section: The Basal Bodymentioning
confidence: 99%
“…Arcobacter species [47], observations supported by purification of disks [48,49]. Recent work in C. jejunihas 119 shown that the cell pole itself has a polar depression into which the hook attaches [39,40,50].…”
mentioning
confidence: 92%
“…The presence of epsilon-proteobacteria in oilfields [57,58] In sum these questions will add to our understanding of epsilonproteobacteria motility, but also fundamentals 182 of the mechanics of the bacterial flagellar motor, and molecular evolution. 183 proteobacterialflagellar motors for H. mustelae [37], C. coli [50], C. fetus(left) [49], (right) [50], (b) freeze-193 fracture images reveal 17 'studs' likely to be stator complexes in H. felis [30]and H. muridarium [34]. Highlights for Beeby, "Motility in the epsilon-proteobacteria"  Epsilon-proteobacteria inhabit animal digestive tracts or environmental niches.…”
mentioning
confidence: 99%